Gravitational instability of vacuum and the cosmological problem - Fomin, P.I. (Вопросы атомной науки и техники, 2013)
It is shown that, with the account of the gravitational interaction, the physical vacuum can spontaneously partially "dissociate" into particles and antiparticles without violation of any conservation laws. Possible cosmological significance of this effect is discussed. A "vacuum cosmological model" is formulated, in which vacuum is taken as the initial state of the Metagalaxy. A generalization of the classical cosmological Einstein equations is made which allows one to take into account phenomenologically the e®ect of gravitational instability of vacuum.
This work was reported at the seminar of the Department of the Theory of Gravity on January 26, 1973.
(The seminar is lead by K. A. Piragas). Показано, що при врахуваннi гравiтацiйної взаємодiї, физiзичний вакуум спроможний без порушення будь-яких законiв збереження спонтанним способом частково "дисоцiювати" начастинки та античастинки. Обговорюється можливе космологiчне значення цього ефекта. Формулюється "вакуумна космологiчна модель", в якiй вакуум приймається за початковий стан Метагалактики. Зроблено узагальнення класичних космологiчних рiвнянь Ейнштейна, якi дозволяють феноменологiчно врахувати ефект гравiтацiйної нестiйкостi вакуума.
Работа доповiдалась на семинарi вiддiлу теорiї гравiтацiї 26.01.1973 p.
(Керiвник семiнару К.А. Пiрагас). Показано, что при учете гравитационного взаимодействия, физический вакуум способен без нарушения каких-либо законов сохранения спонтанным образом частично "диссоциировать" на частицы и античастицы. Обсуждается возможное космологическое значение этого эффекта. Формулируется "вакуумная космологическая модель", в которой вакуум принимается за начальное состояние Метагалактики. Сделано обобщение классических космологических уравнений Эйнштейна, позволяющие феноменологически учесть эффект гравитационной неустойчивости вакуума.
Работа доложена на семинаре отдела теории гравитации 26.01.1973 г.
(Руководитель семинара К.А. Пирагас).